Dual solutions of stagnation-point flow of a fluid on a shrinking surface of another quiescent fluid - Mohd Rohni, Azizah; Omar, Zurni; Man, Noraziah (2015)
A problem of an orthogonal stagnation point flow for an incompressible two-dimensional impingement of a lighter fluid on the surface of a heavier fluid is considered.The governing equations in partial differential equations are first transformed into ordinary differential equations using similarity transformation.The resulting equations are then solved numerically using shooting technique.It is found that dual solutions exist for certain parameters considered.